“If a Muslim says ‘homo’, nothing gets done”: racist discourse and in-group identity construction in an LGBT youth group - Jones, Lucy (Cambridge University Press, 2016)
This article presents ethnographic data emerging from research with a group of LGBT young people, detailing the construction of a shared identity. Using discourse analysis, it shows how the group members position people of South Asian descent as a homogenous out-group, one framed as ‘other’ to their own in-group identity of ‘non-Asian’ due to the assumption that Asian people are homophobic. It is argued that this very local form of identity construction is facilitated by broader discourses of Islamophobia, as well as homonormative ideologies positioning gay people as white. The article therefore provides evidence to support Bucholtz and Hall’s (2005) claim that identity positioning relates not only to the interactional moment and the norms of a given ethnographic context, but that it also encompasses macrolevel discourses and ideologies. It also, however, reveals the pervasiveness of Islamophobic discourses in Britain today, and the marginalisation of LGBT people of colour.